Glycosaminoglycans located on neutrophils and monocytes impact on CXCL8- and CCL2-induced cell migration. (June 2021) - Gerlza, Tanja; Nagele, Margareta; Mihalic, Zala; Trojacher, Christina; Kungl, Andreas
Abstract: The role of glycosaminoglycans on the surface of immune cells has so far been less studied compared to their participation in inflammatory responses as members of the endothelium and the extracellular matrix. In this study we have therefore investigated if glycosaminoglycans on immune cells act in concert with GPC receptors (i.e. both being cis -located on leukocytes) in chemokine-induced leukocyte mobilisation. For this purpose, freshly-prepared human neutrophils and monocytes were treated with heparinase III or chondroitinase ABC to digest heparan sulfate -chains or chondroitin sulfate-chains, respectively, from the leukocyte surfaces. Subsequent analysis of CXCL8- and CCL2-induced chemotaxis revealed that leukocyte migration was strongly reduced after eliminating heparan sulfate from the surface of neutrophils and monocytes. In the case of monocytes, an additional dependence of CCL2-induced chemotaxis on chondroitin sulfate was observed. We compared these results with the effect on chemotaxis of a heparan sulfate masking antibody and obtained similarly reduced migration. Following our findings, we postulate that glycosaminoglycans located on target leukocytes act synergistically with GPC receptors on immune cell migration, which is further influenced by glycosaminoglycans located on the inflamed tissue (i.e. trans with respect to the immune cell/GPC receptor). Both glycosaminoglycan localization sites seem to be important during inflammatory processes and could potentially be tackled in chemokine-related diseases.